ANALISIS PEMANFAATAN PLATFORM E-LEARNING MENGGUNAKAN FRAMEWORK COBIT 5 PADA DOMAIN DSS - Afifah, Ummul Fitri; Verdian, Ihsan (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
This study aims to determine the level of capability of using E-Learning at Universal University. In this study, the measurement of capability level uses the COBIT 5 framework which is devoted to the DSS05 (Manage Security Services) process. The data from this study were obtained from observations and interviews. The results show that the capability level in the DSS05 (Manage Security Services) process reached level 1 with a rating level of Largely achieved (57.8%). After knowing the level of capability at the E-Learning level,recommendations for improvement are made based on the acquisition of each value. The recommendations for improvement are the creation of SOPs related to E-Learning security at Universal University, the establishment of information technology asset inventory management, and the procurement of intrusion detection tools.